2021
DOI: 10.1002/nbm.4568
|View full text |Cite
|
Sign up to set email alerts
|

Brain metabolism in tau and amyloid mouse models of Alzheimer's disease: An MRI study

Abstract: Alzheimer's disease (AD) is the leading cause of cognitive impairment and dementia in elderly individuals. According to the current biomarker framework for “unbiased descriptive classification”, biomarkers of neurodegeneration, “N”, constitute a critical component in the tri‐category “A/T/N” system. Current biomarkers of neurodegeneration suffer from potential drawbacks such as requiring invasive lumbar puncture, involving ionizing radiation, or representing a late, irreversible marker. Recent human studies ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 75 publications
0
18
0
Order By: Relevance
“…The rTg4510 transgenic mouse, an increasingly popular AD model, reported severe hippocampal and neocortical atrophy with concomitant increased ventricles [ 137 ], where females had larger volume decrements than males and both sexes were reduced significantly compared to WT [ 138 ]. Other AD mouse models, such as ApoE4 (24 months), Tau4RDeltaK and Tg4–42 mice, also exhibited significant hippocampal and whole brain volume decrements [ 139 , 140 , 141 ].…”
Section: Magnetic Resonance Findings In Other Ad Mouse Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rTg4510 transgenic mouse, an increasingly popular AD model, reported severe hippocampal and neocortical atrophy with concomitant increased ventricles [ 137 ], where females had larger volume decrements than males and both sexes were reduced significantly compared to WT [ 138 ]. Other AD mouse models, such as ApoE4 (24 months), Tau4RDeltaK and Tg4–42 mice, also exhibited significant hippocampal and whole brain volume decrements [ 139 , 140 , 141 ].…”
Section: Magnetic Resonance Findings In Other Ad Mouse Modelsmentioning
confidence: 99%
“…The decreased CBF in 12-month-old TgCRND8 mice was confirmed and reflected by reduced glucose metabolism without changes in cerebral blood volume [ 88 ]. Finally, the Tau4RDeltaK mouse model showed no change in CBF, which the authors ascribed to normal vascular function despite reduced global oxygen extraction fraction and cerebral metabolic rate [ 140 ].…”
Section: Magnetic Resonance Findings In Other Ad Mouse Modelsmentioning
confidence: 99%
“… Kindler et al (2021) showed a comparable cortical and hippocampal CBF between pR5 mice and wild-type mice at 10 and 18 months of age. Wei et al (2021) reported a reduced cerebral metabolic rate of oxygen while preserving CBF in Tau4RΔK (Tau) mice at 12 months of age compared with wild-type mice by using T 2 relaxation under spin tagging, phase contrast, and ASL MRI. For cerebral vascular response quantification, pulsed ASL and pseudocontinuous ASL methods have been utilized.…”
Section: Functional Imagingmentioning
confidence: 99%
“…Wei et al (2021) reported a reduced cerebral metabolic rate of oxygen while preserving CBF in Tau4R K (Tau) mice at 12 months of age compared with wild-type mice by using T 2 relaxation under spin tagging, phase contrast, and ASL MRI.…”
mentioning
confidence: 99%
“…5×FAD mice [135] MRS TgF344 rats [132] J20 mice [109] APP/PS1 mice [121][122][123][124][125][126] 5×FAD mice [130] 3×Tg mice [129] APPswe mice [127,128]. APP/PS2/Tau mice [131] TASTPM mice [131,167] APP/PS1 mice [105,125,164,168,236] McGill-R-Thy1-APP rats [162] mice [250,251] APP-Au mice [252] 3×Tg mice [93,165,253] APPswe mice [244] APP/PS1KI mice [166] APP/TTA mice [254] DKI APP/PS1 mice [184] 3×Tg mice [188] qMTI APPswe mice [178] DTI TgF344 rats [183] APPswe mice [175,178,186,255] PDAPP mice [176] App NL-G-F knock-in mice [72] APP/PS1 mice [123,171,179,187,189,256] APP23 ...…”
Section: Declaration Of Interestmentioning
confidence: 99%